Efficacy and safety of prucalopride in the treatment of chronic constipation - Kanaki, Anand R.; Kanaki, Asharani A.; Singanal, Sharanabasappa (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Chronic constipation is a common condition that significantly impacts health care utilization, productivity, and quality of life. Laxatives are commonly used, although often insufficient in restoring normal bowel function or providing adequate relief. There remains a significant need for the development of novel agents to optimize treatment of this condition. Prucalopride, a selective, high-affinity 5-hydroxytryptamine 4 receptor agonist, stimulates gastrointestinal and colonic motility and alleviates common symptoms of chronic constipation. Here authors are evaluating efficacy and safety study of this drug in chronic constipation patient. Methods: This is a prospective observational study where chronic constipation patient treated with prucalopride 2 mg daily once were enrolled during 6 month period. Data at one week and four weeks were observed along with adverse effects. Efficacy assessed by the number of Spontaneous Complete Bowel Movements (SCBMs) per week recorded by patient diaries. Patients were defined as responders when they had a mean of three or more SCBMs per week over the whole treatment period. The primary efficacy end point was proportion of responders after 1 week and after 4 weeks of treatment. Results: A total of 43 patients diagnosed with chronic constipation and treated with prucalopride were included in study. The proportions of patients in the present study with at least three SCBMs per week (responders) were 44.2% (19 out of 43 patients) at 1 week and 46.5% (20 out of 43 patients) at 4 weeks. Treatment was well tolerated with minimal side effects. Common adverse effects reported in our study were gastrointestinal disorders like diarrhea, nausea and abdominal pain and nervous system disorders like headache and dizziness. Conclusions: Prucalopride is effective, has a good safety profile, and is well tolerated in chronic constipation treatment.